Development of a degrader against oncogenic fusion protein FGFR3-TACC3. (15th March 2022) - Shibata, Norihito; Cho, Nobuo; Koyama, Hiroo; Naito, Mikihiko
Graphical abstract: Abstract: Fibroblast growth factor receptor 3-transforming acidic coiled-coil containing protein 3 (FGFR3-TACC3), which has been identified in many cancers such as glioblastoma and bladder cancer, is a potent oncogenic fusion protein that induces constitutive activation of FGFR signaling, resulting in uncontrolled cell proliferation. Although several tyrosine kinase inhibitors against FGFR are currently under development, resistance to such types of inhibitors in patients has become a concern. In this study, a chimeric molecule SNIPER(TACC3)-11 (5a ) was developed and found to reduce FGFR3-TACC3 levels effectively. Compound 5a conjugated KHS108 (a TACC3 ligand) to an LCL161 derivative (11 ) (an inhibitor of apoptosis protein [IAP] ligand) with a PEG linker (n = 2). Mechanistical analysis showed that cellular IAP1 was required for the reduction of FGFR3-TACC3 levels. Consistent with the decrease in FGFR3-TACC3 levels, compound 5a suppressed the growth of FGFR3-TACC3 positive cells. Thus, compound 5a is a candidate therapeutic with a novel drug modality against cancers that exhibit FGFR3-TACC3-dependent proliferation and exerts pharmacological effects distinct from FGFR3 kinase inhibitors because it lacks substructures crucial for kinase inhibition.